Eficácia e segurança da indução percutânea de colágeno por agulhas no tratamento da alopecia frontal fibrosante - Lopes, Emily Mourão Soares (2022)
Frontal fibrosing alopecia is a type of cicatricial alopecia first described in 1994. It has been increasingly diagnosed in medical practice. This disease affects mostly postmenopausal women, with a substantial negative impact on patients' quality of life due to irreversible hair loss and a progressive frontotemporal hairline recession that may extend to the retroauricular region, in addition to partial loss of the eyebrows. Its etiology remains unclear and therapeutic options are limited. The use of percutaneous collagen induction therapy has shown promising results in the treatment of other diseases such as alopecia areata and androgenetic alopecia, through stimulation of capillary growth induced by microinjury. Its efficacy may be related to stimulation of the dermal papillae, as well as increased blood supply and recruitment of growth factors. In this study, we aimed to evaluate the efficacy and safety of microneedling technique in frontal fibrosing alopecia. A non-controlled clinical trial was performed with 16 patients at Hospital Universitário Walter Cantidio. They underwent 4 microneedling sessions with an interval of approximately 4 weeks. Each patient was evaluated at baseline, before each session, before every session and after 4 weeks and 12 weeks after the last session. Assessments included measurements of the frontotemporal recess, photographic and trichoscopic evaluations and Dermatology Life Quality Index (DLQI). Lichen planopilaris severity index (LPPAI) was also used to measure disease activity. Although we observed an individual increment in measurements between frontotemporal hairline and established points, the mean value of the distances obtained between the baseline visit and the visit at 12 weeks after the ending of the sessions remained stable (glabella – baseline visit: 8,2 cm, post -12 week: 8,2 cm; right eyebrow – baseline visit : 4,6 cm, post -12 week: 4,5 cm; left eyebrow – baseline visit: 4,5 cm, post -12 week: 4,4 cm; upper right midpoint: 7,0 cm – baseline visit, post-12 week: 7,1 cm; upper left midpoint – baseline visit: 7,0 cm, post -12 week: 7,0 cm). When comparing baseline and last visit, there was a reduction in DLQI (baseline visit: 4,4, post- 12 week: 1,3, p = 0,004) and LPPAI (baseline visit: 1,5, post-12 week: 1,1, p = 0.09). Although we observed a small progression of frontotemporal recession in most patients of the study, improvement in quality of life and inflammatory activity of the diasease point out the need of further studies involving this type of treatment also in FFA and other cicatricial alopecias.